Design and application of personalized surgical guides to treat complex tibial plateau malunion. Issue 4 (29th June 2020) - Hsu, Chi-Pin; Lin, Shang-Chih; Nazir, Aamer; Wu, Chen-Te; Chang, Shih-Sheng; Chan, Yi-Sheng
Abstract: Intra-articular corrective osteotomy can be used to restore the anatomic position of knee surfaces for tibial plateau malunion (TPM) but precise restoration is not easy. The personalized surgical guide (PSG) might improve the TMP outcomes. This study developed a two-staged PSG method to provide registration and drill the bone for subsequent osteotomy. The tests were performed to compare the accuracy the proposed PSG and the conventional guide (Anterior cruciate ligament guide, ACLG). The results showed that the PSG provides better accuracy (0.50 ± 0.19 mm) than the ACLG (1.58 ± 0.67 mm). The results show the PSG method is a feasible alternative to the conventional ACLG procedure.